# Limit simplification

I've been practicing limits today, and I've came across this exercise which confused me a bit:

$\lim_{x\to -3} \frac{(x^2-9)^2}{(x+3)^2}$

My approach was to do this:

$\lim_{x\to -3} \frac{(x^2-9)^2}{x^2+3x+9}$

$\lim_{x\to -3} \frac{0}{9}$

Can anyone explain why this is not a valid approach? I realised that as long as the denominator is not 0, I can start inserting the x.

The valid solution is 36, and I know how to get there, I just don't get it why my approach is wrong.

Thanks!

Note that

$$\lim_{x\to -3} \frac{(x^2-9)^2}{x^2+\color{red}6x+9}$$

We can solve in this way

$$\lim_{x\to -3} \frac{(x^2-9)^2}{(x+3)^2}=\lim_{x\to -3} \frac{(x-3)^2(x+3)^2}{(x+3)^2}=\lim_{x\to -3} (x-3)^2=36$$

• I guess I don't have to rush over an exercise anymore... Because this is what happens. Thanks!
– Dino
Mar 23, 2018 at 0:00
• @Dino You are welcome! Don't worry, today I had at least 3 or 4 similar oversight! Bye
– user
Mar 23, 2018 at 0:02

\begin{align} x^2 - 9 &= x^2 - 3^2 \\ \\ &= (x+3)(x-3) \\ \Rightarrow \dfrac{(x^2-9)^2}{(x+3)^2} &= \dfrac{\require{cancel}\cancel{(x+3)^2}(x-3)^2}{\cancel{(x+3)^2}} \\ &= (x-3)^2. \\ \\ \therefore \lim_{x\to -3}\frac{(x^2-9)^2}{(x+3)^2} &= \lim_{x\to -3} (x-3)^2 \\ \\ &= (-3 - 3)^2 \\ \\ &= 36.\end{align}